PS-C30-14: A CASE OF PREECLAMPSIA DIAGNOSED BY RENAL BIOPSY. (January 2023) - Koshida, Takeo; Suzuki, Hitoshi; Iwasaki, Masako; Umezawa, Yukako; Yoshida, Maiko; Hamaguchi, Sho; Fukuda, Hiromitsu; Takahara, Hisatsugu; Tomita, Shigeki; Suzuki, Yusuke
Abstract : Preeclampsia is a complicat ion of pregnancy. With preeclampsia, the patients show high blood pressure and high levels of proteinuria. Preeclampsia usually begins after 20 weeks of pregnancy in women whose blood pressure had previously been in the standard range. If the patients left untreated, preeclampsia can lead to serious complications for both the mother and baby. Meanwhile, focal segmental glomerulosclerosis (FSGS) is also need to be discriminated in pregnant women with massive proteinuria. A 32-year-old woman has not been recognized hypertension, and has never been pointed out any urinary abnormality in a medical checkup. Her blood pressure gradually increased at 30 weeks of gestation. At 34 weeks gestation, blood pressure was 180/108 mmHg with medication, and she was detected proteinuria. Even after delivery, massive proteinuria (13.7 mg/gCr) was detected without microscopic hematuria. Then, renal biopsy was performed for definitive diagnosis. Histological findings showed focal endotheliosis of the glomeruli and double contour in which are the typical histological findings for preeclampsia. High levels of proteinuria after delivery is important index for medical treatment. Present case was diagnosed as preeclampsia by renal biopsy resulted in keep antihypertensive treatment without any immunosuppressant. The histological implication on our clinical management of preeclampsia may be profound for understanding of strict control of blood pressure during perinatal period.